Diversity of brain metastases screening and management in non-small cell lung cancer in Europe: Results of the European Organisation for Research and Treatment of Cancer Lung Cancer Group survey. (April 2018) - Levy, Antonin; Faivre-Finn, Corinne; Hasan, Baktiar; De Maio, Eleonora; Berghoff, Anna S.; Girard, Nicolas; Greillier, Laurent; Lantuéjoul, Sylvie; O'Brien, Mary; Reck, Martin; Dingemans, Anne-Marie C.; Novello, Silvia; et al.
Abstract: Background: Brain metastases (BM) are frequent in non-small cell lung cancer (NSCLC) patients, but there is a lack of evidence-based management of this patient group. We aimed to capture a snapshot of routine BM management in Europe to identify relevant research questions for future clinical trials. Methods: An EORTC Lung Cancer Group (LCG) online survey containing questions on NSCLC BM screening and treatment was distributed between 16/02/17 and 15/06/17 to worldwide EORTC LCG members, and through several European scientific societies in the thoracic oncology field. Results: A total of 462 European physician responses (394 institutions) were analysed (radiation oncologist: 53% [n = 247], pulmonologist: 26% [n = 119], medical oncologist: 18% [n = 84]; 84% with >5 years' experience in NSCLC). Italy (18%, n = 85), Netherlands (15%, n = 68), UK (14%, n = 66), and France (12%, n = 55) contributed most. 393 physicians (85%) screened neurologically asymptomatic patients for BM at diagnosis (52% using magnetic resonance imaging). Most often screened patients were those with a driver mutation (MUT+; 51%, n = 234), stage III (63%, n = 289), and IV (43%, n = 199). 158 physicians (34%) used a prognostic classification to guide initial treatment decisions, and in 50%, lowest prognostic-score threshold to receive treatment differed between MUT+ and non-driver mutation (MUT−) patients. MUT+ patients with >4 BM were more likely to receive stereotactic radiosurgery (SRS) compared with MUT− (27% versus. 21%; p < 0.01). Most physicians (90%) had access to SRS. After single BM surgery, 50% systematically prescribed SRS or WBRT, and 45% only in case of incomplete resection. The preferred treatment in neurologically asymptomatic treatment-naive patients diagnosed with >5 BM was systemic treatment (79%). Of all, 45%/49% physicians stated that all tyrosine kinase inhibitors and immune checkpoint blockers were discontinued (timing varied) during SRS/WBRT, respectively. Drugs most often continued during SRS/WBRT were erlotinib (44%/40%), gefitinib (39%/34%), afatinib (29%/25%), crizotinib (33%/26%) and anti-PD-(L)-1 (28%/22%). Conclusion: BM management is highly variable in Europe: screening is not uniform, prognostic classifications are not often used and MUT+ NSCLC patients generally receive more intensive local treatment. Prospective assessment of BM management in MUT+ NSCLC patients is required. Highlights: This EORTC survey found that European BM management is not according to European guidelines. BM screening is not uniform, prognostic classifications are not often used, and MUT + NSCLC patients receive more intensive local treatment. Efforts in harmonisation of management of BM should be pursued by cancer societies. For MUT + NSCLC patients, specific BM guidelines and trials are required.